Unveiling the structuring effects of eutrophication on macrobenthic biological traits in Hangzhou Bay and adjacent waters - Zhou, Weiwei; Wang, Xiaobo; Han, Qingxi (Frontiers in Marine Science, 2024)
The ecological effects of eutrophication on estuaries and coastal ecosystems are significant worldwide. Based on data collected in 2019 from Hangzhou Bay and adjacent waters, this study employed biological traits analysis and RLQ/fourth-corner analysis methods to investigate the distribution patterns of macrobenthic assemblages along a eutrophication gradient and reveal the response patterns of their biological traits to eutrophication stress. The results showed that eutrophication had a significant structuring effect on the spatial distribution of macrobenthic community structure. As the level of eutrophication increased, the community abundance and number of macrobenthic biological traits decreased. The composition of macrobenthic community biological traits changed in response to eutrophication. In areas with high levels of eutrophication, larger body sizes became more dominant, reflecting a shift in dominant traits similar to the eutrophication gradient. Furthermore, the predominant species in this region were burrowers and tube dwellers, which preferred muddy sand and sandy mud substrates. The AMBI ecological group accurately reflects the degree of eutrophication disturbance, with tolerant species and second-order opportunistic species being common in eutrophic areas.